How to cheat at securing SQL server 2005 (Syngress, 2007)
SQL Server is the perfect product for the How to Cheat series. It is an ambitious product that, for the average SysAdmin, will present a difficult migration path from earlier versions and a vexing number of new features. How to Cheat promises help in order to get SQL Server secured as quickly and safely as possible.